A sea change: Johan Hjort and the natural fluctuations in the fish stocks - Schwach, Vera (ICES Journal of Marine Science, 2014)
That recruitment of juveniles to the stocks of fish is subject to natural variations is considered a scientific truth, if not a truism, in marine science. However, in 1914, when the zoologist Johan Hjort (1869–1948) published the notion, it meant a basic change in the understanding of the biology of the sea fish. A century later, his insight is a topic still at the centre of interest in fish biology. Hjort based his concept largely on investigations of herring ( Clupea harengus ) and cod ( Gadus morhua ) in the North Atlantic. He was the mastermind, but worked with a small group at the Directorate of Fisheries in Bergen, Norway, and in cooperation with the International Council for the Exploration of the Sea (ICES). The theory of natural fluctuations prompted an important step from migration thinking to population thinking, and gave the emerging fish biology and multidisciplinary marine science a theoretical basis. The article aims to explore the set of important facts and reasoned ideas intended to explain the causes for variations in year classes, and in this the fluctuations in the recruitment to the stocks. It argues that in addition to scientific factors, economic and political circumstances had an important say in the shaping of the understanding of stock fluctuations. The mere existence of a theory does not alone account for a breakthrough, and the article draws attention to the acceptance of scientific results.